Outage Performance of Free-Space OpticalCommunication Systems Over Turbulent Channels with Varying Atmospheric Visibilities - Rahat Ara; It Ee Lee; Zabih Ghassemlooy; Gwo Chin Chung; Muhammad Sheraz; Teong Chee Chuah (International Journal of Integrated Engineering, 2025)
Free space optics is the technology where beams of light provide optical connection using a line-of-sight path for communication as a form of video, voice, and data information between two points. A few of the FSO system's limitations include atmospheric attenuation caused by weather, which is the most difficult issue to solve because it seriously impairs system performance and results in poor signal transmission. One of the important performance measures for analyzing and enhancing FSO functionality for various fading states associated with different data rates is outage probability. This article examines FSO in terms of transmission optical power, feasible bit rates, and outage probability under clear, hazy, and moderate to heavy rainy conditions. The MATLAB simulation is implemented to do the performance study. However, aperture diameters D = 20, 40, 80, 100 mm and link distances L = 2.0, 3.5, 5.0 mm are seen to be essential characteristics for evaluating system performance. For all scenarios, the system's power consumption can be minimized by using larger aperture diameters at lower bit rates, particularly in clear weather.